Women's Status in Changing Agrarian Relations: A Kerala Experience - K. Saradamoni (Economic and Political Weekly, Vol. 17, No. 5 (Jan. 30, 1982), pp. 155-157+159-162, 1982)
This paper examines the chianges brought about in the lives and status of twontet by changes in the agrarian structure. The area studied is Palghat district in Kerala. The authlor examines how the progressive break- down of landlordlism in Palghat and the accompanying socio-cultural changes affected wvomen belonging to different strata of the agricultural commuinity